The role of families and pre-school in educational disadvantage - Sylva, K (Routledge, 2014)
In the first volume of the Oxford Review of Education Jerome Bruner (1975) showed how the upbringing of the very young is influenced by poverty, and how different kinds of upbringing shape human development. He called the paper ‘Poverty and childhood’ and baldly stated ‘With respect to virtually any criterion of equal opportunity and equal access to opportunity, the children of the poor.. are plainly not getting as much schooling, or getting as much from their schooling as their middle-class age mates’ (p. 43). Since Bruner’s seminal paper, the developmental sciences have exploded. New insights from neuroscience, genetics and cognitive psychology have provided accounts of the developing architecture of the brain, the course of linguistic and cognitive development, and more recently the development of resilience. Most of these insights focus on the development of the child, but usually from research in the laboratory or in the context of the family. However, there is also a new literature on ways that environments outside the home can support or hinder the child’s development. This paper will attempt to integrate findings from the developmental sciences with educational research on pre-school education. The first half of the paper extends Bruner’s arguments through a discussion of possible mechanisms that underlie the link between poverty and under-achievement, especially the capacity to plan ahead. The second half of the paper focuses on the role of the ‘enabling environment’ of the pre-school in supporting the kinds of early ‘executive functions’ that will later underpin educational achievement. The paper concludes with recent findings from the ‘Effective Pre-school, Primary and Secondary Education’ research (EPPSE; Sylva, Melhuish, Sammons, Siraj, and Taggart, 2014) on the educational pathways of nearly 3000 English children. The findings show that high quality pre-school provided the foundation for academic learning, but the newest research shows that it also nurtured self-regulation and the executive skills needed in planning ahead.